2006
DOI: 10.1152/ajpheart.01012.2005
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular lactate as a dynamic vasoactive signal in the rat retinal microvasculature

Abstract: We tested the hypothesis that extracellular lactate regulates the function of pericyte-containing retinal microvessels. Although abluminally positioned pericytes appear to adjust capillary perfusion by contracting and relaxing, knowledge of the molecular signals that regulate the contractility of these mural cells is limited. Here, we focused on lactate because this metabolic product is in the retinal extracellular space under both physiological and pathophysiological conditions. In microvessels freshly isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 25 publications
9
119
0
Order By: Relevance
“…5). Also similar to hypoxia and consistent with lactate's role as a vasodilator in the normal retinas (15,(19)(20)(21), arterioles within both control and >P40 ROP retinas-whose vessels were not suprahyperpolarized (Fig. 1C)-dilated in response to lactate (Fig.…”
Section: Electrogenic Basis For Neovesselsupporting
confidence: 70%
See 1 more Smart Citation
“…5). Also similar to hypoxia and consistent with lactate's role as a vasodilator in the normal retinas (15,(19)(20)(21), arterioles within both control and >P40 ROP retinas-whose vessels were not suprahyperpolarized (Fig. 1C)-dilated in response to lactate (Fig.…”
Section: Electrogenic Basis For Neovesselsupporting
confidence: 70%
“…Based on our earlier study of retinovessels (20), we considered a role for a cascade of events involving lactate, MCT, and NCX. Previously, we found that under certain conditions, the activation of this cascade can cause retinovessels to contract (20), although this vasoconstricting influence is usually vitiated by the potent vasorelaxing impact of lactate on precapillary arterioles (21), as well as on larger retinal arterioles, in which the activation of a voltage-changing K ATP current plays a key role (15). However, we posited that the relative impact of the lactate/MCT/NCX pathway would be boosted when suprahyperpolarization to a voltage near E K , as observed in <P30 ROP retinas (Fig.…”
Section: Electrogenic Basis For Neovesselmentioning
confidence: 99%
“…Several studies have reported that lactate increases vasodilation by different mechanisms (Hein et al, 2006;Yamanishi et al, 2006;Gordon et al, 2008), and continuous lactate release from the activated brain may serve a signaling function to increase blood flow and fuel delivery to the brain. As glucose delivery to the brain exceeds demand for glucose over a wide range of CMR glc (Cremer et al, 1983;Hargreaves et al, 1986), lactate release and its use as a blood flow regulator need not be a 'waste' of fuel, because lactate can be used by peripheral tissues as fuel or as a gluconeogenic substrate.…”
Section: Lactate Can Stimulate Vasodilationmentioning
confidence: 99%
“…The sites of pericyte/endothelial interactions are altered in pathological disease. In diabetes and cerebral oedema, gap junctions are substantially decreased in the retina and disrupted in retinal pericytes (Yamanishi et al, 2006), indicating the importance of pericyte-endothelial cell communication for adaptability to injury.…”
Section: Angiogenesismentioning
confidence: 99%